Hibridação e identificação de genes envolvidos na senescência de gérbera visando o silenciamento de genes e melhoramento genético - Cardoso, Raquel Dalla Lana (2012)
The Brazilian production of gerbera (Gerbera hybrida Hort.) is dependent of multinational companies that perform the breeding process and provide genetic materials for the internal market. Thus, the development of national breeding programs could help to reduce this dependence, to obtain adapted cultivars to Brazilian environmental conditions and improve yield. Information about hybridization techniques are not published because of the commercial importance and due to the fact that breeding is executed by private companies. Studies to understand the reproductive system of gerbera have been made but the seed production in hybridizations has been low. This work was carried out to provide subsidies for the breeding of gerbera, helping to reduce the current dependence of flowers cultivars sold in the country. Three studies were performed: artificial hybridization and its effect on seed formation and analysis of progeny obtained, carried out in semi-protected environment at UPF; evaluation of the expression of transcripts expressed sequence tags and genes related to flower senescence; evaluation of virus-induced gene silencing technique, carried out at the University of California, Davis-USA. The occurrence of geitonogamy and no self-incompatibility were confirmed. The influence the general and specific combining ability for the formation of seeds was not significant. It was possible to generate segregant populations and high herdability was found for most floral traits evaluated. Sixteen expressed sequence tag and six senescence associated gene were evaluated, thirteen were up regulated and four down regulated with advancing stages of senescence. The virus-induced gene silencing can be used, however, must be optimized to obtain a more effective gene silencing and be applied in studies for identification of gene function.